Males Are Overrepresented among Life Science Researchers Committing Scientific Misconduct - Ferric C. Fang (American Society for Microbiology, 2013)
ABSTRACT A review of the United States Office of Research Integrity annual reports identified 228 individuals who have committed misconduct, of which 94% involved fraud. Analysis of the data by career stage and gender revealed that misconduct occurred across the entire career spectrum from trainee to senior scientist and that two-thirds of the individuals found to have committed misconduct were male. This exceeds the overall proportion of males among life science trainees and faculty. These observations underscore the need for additional efforts to understand scientific misconduct and to ensure the responsible conduct of research. IMPORTANCE As many of humanity’s greatest problems require scientific solutions, it is critical for the scientific enterprise to function optimally. Misconduct threatens the scientific enterprise by undermining trust in the validity of scientific findings. We have examined specific demographic characteristics of individuals found to have committed research misconduct in the life sciences. Our finding that misconduct occurs across all stages of career development suggests that attention to ethical aspects of the conduct of science should not be limited to those in training. The observation that males are overrepresented among those who commit misconduct implies a gender difference that needs to be better understood in any effort to promote research integrity.